Value Based Crisis Management in Islamic Education Management: Typology, Multidimensional Impacts, and An Integrated Model - Syawal, Ahmad; Agustin, Nadilla Aleyda Maqhfira; Adzillah, Salsabila Nur Imatul; Lestari, Futry Ayu; Musdalifa (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This study examines the typology of crises, their multidimensional impacts, and the urgency of crisis management within Islamic Education Management (MPI) from a value-based perspective. The research adopts a qualitative literature review methodology to systematically synthesize theoretical and empirical studies related to crisis management, Islamic educational governance, and budget efficiency. Academic publications indexed in major scholarly databases were analyzed thematically to identify crisis patterns, impact dimensions, and value-oriented management responses. The findings reveal that crises in MPI can be categorized into internal and external types, both of which are shaped by complex interactions between managerial, social, and spiritual factors. Internal crises are closely associated with leadership conflicts, moral deviations, and financial inefficiencies, particularly budget efficiency policies that marginalize core Islamic educational programs, while external crises arise from environmental uncertainty, digital public pressure, natural disasters, and regulatory changes. The impacts of these crises are inherently multidimensional, affecting academic quality, psychological well-being, social trust, and spiritual identity simultaneously. The study highlights that neglecting Islamic values in crisis management risks not only operational disruption but also long-term erosion of institutional identity and legitimacy. Theoretically, this study advances crisis management discourse by positioning spiritual values as a central analytical dimension in faith-based institutions. Practically, it underscores the need for integrated crisis management strategies that align modern managerial practices with Islamic principles. The study is limited by its reliance on secondary data and the absence of empirical case analysis. Future research is recommended to empirically test the proposed integrated model across diverse Islamic education settings and to explore its long-term implications for institutional resilience.